2015
DOI: 10.1007/978-3-319-16537-0_3
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Stem Cells from Human Central Nervous System Malignancies

Abstract: Central Nervous System (CNS) tumors include some of the most invasive and lethal tumors in humans. The poor prognosis in patients with CNS tumors is ascribed to their invasive nature. After the description of a stem cell-like cohort in hematopoietic cancers, tumor stem cells (TSCs) have been isolated from a variety of solid tumors, including brain tumors. Further research has uncovered the crucial role these cells play in the initiation and propagation of brain tumors. More importantly, TSCs have also been sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 93 publications
0
4
0
Order By: Relevance
“…Immunohistochemistry. The tumor tissues were fixed in 4% paraformaldehyde, washed with PBS, transferred to 70% ethanol and then embedded in paraffin in accordance with standard procedures (22). The antibodies used in this study were a goat anti-human Cx43 monoclonal antibody (ab87645, 1:2,000; Abcam Trading Company Ltd.) and mouse anti-human SUMO1 monoclonal antibody (sc-5308, 1:400; Santa Cruz Biotechnology).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunohistochemistry. The tumor tissues were fixed in 4% paraformaldehyde, washed with PBS, transferred to 70% ethanol and then embedded in paraffin in accordance with standard procedures (22). The antibodies used in this study were a goat anti-human Cx43 monoclonal antibody (ab87645, 1:2,000; Abcam Trading Company Ltd.) and mouse anti-human SUMO1 monoclonal antibody (sc-5308, 1:400; Santa Cruz Biotechnology).…”
Section: Methodsmentioning
confidence: 99%
“…To further investigate whether Cx43 SUMOylation increases GJIC in liver cancer stem cells, we observed the transmission of Hoechst 33342 in HepG2 cell spheres that were co-transfected with Cx43-wt alone or in combination with GFP-SUMO1. In theory, cancer stem cells are able to efflux the fluorescent dye, Hoechst 33342 (22). Therefore, fluorescence microscopic observations or flow cytometry should detect no staining.…”
Section: Cx43 Is Modified By Sumo1 In Liver Cancer Stem Cellsmentioning
confidence: 99%
“…Glioblastoma Mutliforme (GBM) is the most common primary brain tumor and has a poor prognosis. The average survival rate is approximately 15 months even if the patient surgical resection combined with chemotherapy and radiotherapy [1]. Cell culture is a key technology for cancer research, as it allows scientists to study the biology of tumor cells in an environment with controlled variables [2].…”
Section: Introductionmentioning
confidence: 99%
“…A previous study revealed the existence of tumor stem cells (TSCs), which have the same functions as neural stem cells inside tumor cells including the ability to self-proliferate (3). There are a number of similarities between TSCs and neural stem cells that suggest the origin of TSCs (4), a variety of solid tumors, including brain tumors (5) and expression of numerous similar proteins (6). The discovery of TSCs has provided novel options for the treatment of brain tumors (7), including therapies targeting specific signaling pathways and transcription factors, and niche therapies targeting cancer stem cells (8,9).…”
Section: Introductionmentioning
confidence: 99%